Effect of thermal processing on cholesterol synthesis, solubilisation into micelles and antioxidant activities using peptides of Vigna angularis and Vicia faba. (July 2020) - Ashraf, Jawad; Awais, Muhammad; Liu, Liya; Khan, Muhammad Issa; Tong, Li-Tao; Ma, Yuling; Wang, Lili; Zhou, Xianrong; Zhou, Sumei
Abstract: Bioactive peptides are generally obtained from plant protein hydrolysates. These peptides possess physiological activities, such as lowering blood cholesterol. In the current study, proteins from adzuki bean ( Vigna angularis ) and faba bean ( Vicia faba) were thermally processed, and low molecular weight peptides (<3 kDa) were isolated to assess their efficacy for inhibiting cholesterol synthesis and its solubilisation. High-performance liquid chromatography (HPLC) results showed higher peptide concentrations after thermal processing. Inhibition of cholesterol solubilisation into micelles and 3-hydroxy-3-methylglutaryl coenzyme-A reductase (HMG Co-AR) catalytic activity was evaluated. After processing, the faba bean peptides showed significantly ( p  < 0.05) increased inhibition of cholesterol solubilisation into micelles (45.1 ± 1.6%), whereas peptides from the native faba bean protein exhibited significantly increased ( p  < 0.05) inhibition of HMG Co-AR catalytic activity (84.1 ± 2.7%) compared with the adzuki bean and thermally processed peptides. After processing, the adzuki bean peptides showed significantly reduced scavenging activity compared with peptides obtained from the native protein. This study is the first report demonstrating that the peptides from adzuki and faba beans inhibit cholesterol homeostasis via distinctive ways and act as antioxidants. Highlights: Thermal processing increased degree of hydrolysis and peptides concentration. Thermally processed peptides showed higher inhibition of cholesterol solubility into micelle. It has effect on HMGCR enzymatic activity. Correlation showed highly significant positive correlation of FRAP with 3 KDa peptides concentrations. It also showed significant positive correlation of solubility with hydrolysis and peptides concentration.